Teaching Ottoman History through Teams Games Tournament to Improve Students’ Remembering and Understanding - Ifsya Gita Afrianzi; Zaki Afifi (Universitas Islam Negeri Sumatera Utara, 2026)
Islamic Religious Education (PAI) learning in schools is often dominated by one-way lectures, resulting in passive student participation and limited development of the cognitive abilities of remembering (C1) and understanding (C2). This study aimed to describe the implementation of the Teams Games Tournament (TGT) model and examine its contribution to students’ remembering and understanding of Ottoman history based on the revised Bloom’s Taxonomy. A descriptive qualitative approach with a case study design was employed, involving 28 students from class VIII F at SMPN 2 Colomadu. Data were collected through classroom observations, interviews with six purposively selected students, documentation, and students’ learning outcomes. The data were analyzed through data reduction, data display, and conclusion drawing. The findings indicated that TGT increased students’ participation and learning interest and supported the development of remembering (C1), as demonstrated by their ability to recall historical facts without consulting their notes. TGT also supported understanding (C2), as reflected in students’ ability to explain the role of Sultan Muhammad Al-Fatih and the factors contributing to the progress and decline of the Ottoman Dynasty in their own words. However, its benefits were not experienced equally by all students because participation and comprehension were influenced by individual learning interest. These findings suggest that teachers can use TGT as an interactive alternative to lecture-based instruction while combining it with other methods to accommodate diverse student characteristics. The study also provides empirical insight for developing cooperative and game-based models for teaching Islamic civilization history.